The Role of Multilateral Institutions in Promoting Global Islamic Trade: A Literature Review of Effectiveness and Strategies - Rasyid, Cynthia Nur; Andi Purwanto; Kholis, Nur (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2025)
Global Sharia-based trade is growing in response to the need for a more inclusive, equitable, and sustainable economic system. This article analyzes multilateral institutions that promote global Sharia trade, focusing on strategies, effectiveness, and policy impacts on country development. The research was conducted through a systematic literature review approach and a current case study analysis, integrating three main theories: World Systems (Wallerstein), Institutionalism (North), and Global Governance. The results show that institutions such as the Islamic Development Bank (IsDB), the Organization of Islamic Cooperation (OIC), the World Trade Organization (WTO), and the United Nations Conference on Trade and Development (UNCTAD) play an important role in harmonizing halal standards, facilitating sharia financing, and developing adaptive trade regulations. The results show that these institutions' interventions have increased halal product exports by up to 30%, expanded access to sharia microfinance, and created thousands of jobs in developing countries. However, differences in standards, limited local capacity, and inequality in access to technology remain significant challenges. Therefore, cross-country collaboration and strengthening national institutions are needed to create a cohesive and competitive global Sharia trading ecosystem. This study provides strategic recommendations to strengthen synergy between institutions and support the sustainability of sharia trading in a dynamic global economic landscape.